Dietary fiber intake and head and neck cancer risk: A pooled analysis in the International Head and Neck Cancer Epidemiology consortium. Issue 9 (27th July 2017) - Kawakita, Daisuke; Lee, Yuan‐Chin Amy; Turati, Federica; Parpinel, Maria; Decarli, Adriano; Serraino, Diego; Matsuo, Keitaro; Olshan, Andrew F.; Zevallos, Jose P.; Winn, Deborah M.; Moysich, Kirsten; Zhang, Zuo‐Feng; et al.
Abstract : The possible role of dietary fiber in the etiology of head neck cancers (HNCs) is unclear. We used individual‐level pooled data from ten case‐control studies (5959 cases and 12, 248 controls) participating in the International Head and Neck Cancer Epidemiology (INHANCE) consortium, to examine the association between fiber intake and cancer of the oral cavity/pharynx and larynx. Odds Ratios (ORs) and their 95% Confidence Intervals (CIs) were estimated using unconditional multiple logistic regression applied to quintile categories of non‐alcohol energy‐adjusted fiber intake and adjusted for tobacco and alcohol use and other known or putative confounders. Fiber intake was inversely associated with oral and pharyngeal cancer combined (OR for 5th vs . 1st quintile category = 0.49, 95% CI: 0.40–0.59; p for trend <0.001) and with laryngeal cancer (OR = 0.66, 95% CI: 0.54–0.82, p for trend <0.001). There was, however, appreciable heterogeneity of the estimated effect across studies for oral and pharyngeal cancer combined. Nonetheless, inverse associations were consistently observed for the subsites of oral and pharyngeal cancers and within most strata of the considered covariates, for both cancer sites. Our findings from a multicenter large‐scale pooled analysis suggest that, although in the presence of between‐study heterogeneity, a greater intake of fiber may lower HNC risk. Abstract : What's new? Higher intake of fruit and vegetables is thought to lower the risk of HNCs. These foods are rich in phytochemicals and vitamins, but could dietary fiber also play a role in this protective effect? In this analysis, the authors pooled data from 10 separate studies to examine the association between fiber intake and cancer of the oral cavity/pharynx and larynx. Their results suggest that a greater intake of fiber may indeed lower HNC risk.